Characterization and structure prediction of the 5' untranslated region from Hepatitis C Virus Colombian isolates (2022)
ABSTRACT: The genome of the Hepatitis C Virus (HCV) is a single stranded positive sense RNA flanked by 5’ and 3’ untranslated regions (UTR). The 5’UTR has a relevant role in translation of the HCV polyprotein driven by the internal ribosome entry site (IRES). This structured región contains four domains (DI-DIV) from which DII and DIII have the main role in the interaction to the ribosome, and therefore for initiation of translation. Furthermore, DII presents two subdomains (basal DIIa, and apical DIIb) while DIII consists of 6 stem-loops (DIIIabcdef).